Penerapan Model Problem Based Learning (PBL) Melalui Eksperimen untuk Meningkatkan Pemahaman Konsep Siswa Kelas IV SD Muhammadiyah 8 KH Mansur Kota Malang - Erviani Ratna Ningtyas; Etika Susilowati; Yus Mochamad Cholily (Universitas Islam Lamongan, 2023)
Natural Sciences (IPA) is one of the learning content in the curriculum applied in Indonesia. Science learning is used to train students to have a scientific attitude with sensitivity to the surrounding environment with the acquisition of Science Scientific Concepts in elementary school is very important to build a strong understanding of natural phenomena and the world around them. This research is a type of collaborative Classroom Action Research (PTK) by collaborating between researchers and class teachers. This study uses a qualitative descriptive method by describing an event that occurred at school with the subject of the study, namely grade IV students at SD Muhammadiyah 8 KH Mansur Malang City. Other supporting data in this study are observations, interviews, documentation. Based on the results of research conducted at SD Muhammadiyah 8 KH Mansur Malang City, it can be concluded that after processing student learning outcome data, especially science subjects, researchers analyzed the data using comparative descriptive techniques, namely by comparing the results of pre-cycle, cycle I and cycle II tests. Based on the percentage of learning outcomes with learning using the PBL model with the help of experimental activities, students have a better understanding of science conceptsBased on research that has been done that the application of the Problem Based Learning model assisted by experimental activities using simple tools, namely paper and wax, makes learning done by solving problems through experiments, thus encouraging students to have fun, develop their minds, and actively participate in ongoing learning. Based on the experiments that have been conducted, it can be concluded that thermal energy can be converted into motion energy.